PENGARUH LOKASI TERHADAP REVISIT DENGAN MEDIASI KEPUASAN DAN MODERATOR CITRA RASA DAN HARGA (STUDI KASUS PADA KONSUMEN TEH GELAS DI KAB. BEKASI) - Joni Heruwanto; Mahda Widi Handayani; Ni Made Bunga Kinanti Mara Yasa; Shinta Kezia Sulla; Sinta Siahaan; Surya Bintarti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The high consumer interest in packaged beverages influences the lifestyle and culture in Indonesia. This can be seen from the existence of a company that continues to compete with other packaged beverage companies to prioritize a ready-to-drink tea product, such as the Teh Gelas, Tehbotol Sosro, and Teh Pucuk Harum. The purpose of this study was to examine the effect of the location where packaged drinks were obtained on repurchase or revisit which was mediated by consumer satisfaction and moderated by taste and price image of the Teh Gelas drink managed by Cap Orang Tua (OT). This research uses quantitative methods. The population used by the community in Bekasi Regency, the number of samples obtained was 84 respondents. Data collection is done with secondary and primary data. Data analysis in this study was fully carried out with the help of the SmartPLS 3.0 program. Research proves that price-moderated location has no effect on satisfaction, price-moderated location has no effect on satisfaction, but taste image and price have a partial effect on satisfaction and satisfaction-mediated location has an effect on revisit